Pengaruh Bantuan Sosial terhadap Perilaku Memilih Petahana dalam Pemilihan Walikota Palangka Raya 2024 - Anyualatha Haridison; Bismar Harris Satriawan; Christian Bernard; Jhon Retei Alfri Sandi; Imanuel Jaya (Pusat Riset dan Inovasi Nasional, 2026)
Social assistance programs are often a major concern during local elections. However, their impact on voter support for incumbents remains underexplored. This study analyzes how perceptions of social assistance influence voting behavior for incumbents in the 2024 Palangka Raya mayoral election. Using a sequential explanatory mixed methods design, the quantitative stage was conducted through a survey of 370 social assistance recipients and analyzed using PLS-SEM. The qualitative stage used 13 official documents and verified news reports to examine how social assistance was framed in the public sphere. The results show that perceptions of social assistance are the strongest predictor of the tendency to vote for incumbents, whereas political competition, demographic factors, and moderating effects are not significant. Qualitative analysis shows that social assistance issues are the most frequently mentioned theme in news reports and official documents, thereby reinforcing their relevance as a basis for evaluation by the beneficiaries. This study shows that voters tend to respond to the benefits of policies they perceive in determining their electoral choices, even within a public sphere that frequently raises issues of program politicization.